Strategi Kepemimpinan Kepala Sekolah dalam Upaya Meningkatkan Mutu Pendidikan - Zulkarnaen, Adnan; Asy’ari, Hasyim (Innovative: Journal Of Social Science Research, 2025)
A quality education is one that has the advantage or ability of the education system in managing and processing educational inputs effectively and efficiently so as to produce quality and useful educational outputs to meet customer needs. To improve the quality of education, a principal's leadership strategy must consider the context in which leadership takes place. There are keys to success in implementing possible leadership strategies. These include a complete vision, responsibility, role modeling, providing the best service, developing others, fostering a sense of unity, focusing on learners, practice-first management, adjusting leadership style, and utilizing the power of expertise.